2020
DOI: 10.1210/clinem/dgaa065
|View full text |Cite
|
Sign up to set email alerts
|

Insight Into the Ontogeny of GnRH Neurons From Patients Born Without a Nose

Abstract: Context The reproductive axis is controlled by a network of gonadotropin-releasing hormone (GnRH) neurons born in the primitive nose that migrate to the hypothalamus alongside axons of the olfactory system. The observation that congenital anosmia (inability to smell) is often associated with GnRH deficiency in humans led to the prevailing view that GnRH neurons depend on olfactory structures to reach the brain, but this hypothesis has not been confirmed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…More recently, Delaney and colleagues specifically evaluated the co-occurrence of CHH and arhinia, providing evidence that most patients exhibited clinical and/or biochemical signs of GnRH deficiency. However, a small portion of female patients had normal breast development and menstrual cycles, suggesting a fully intact reproductive axis [192]. These findings, together with previous studies in arhinic mice [15], indicate that the main olfactory system may not be necessary for the migration of GnRH neurons.…”
Section: Structural Maintenance Of Chromosomes Flexible Hinge Domain Containing 1 (Smchd1)mentioning
confidence: 48%
“…More recently, Delaney and colleagues specifically evaluated the co-occurrence of CHH and arhinia, providing evidence that most patients exhibited clinical and/or biochemical signs of GnRH deficiency. However, a small portion of female patients had normal breast development and menstrual cycles, suggesting a fully intact reproductive axis [192]. These findings, together with previous studies in arhinic mice [15], indicate that the main olfactory system may not be necessary for the migration of GnRH neurons.…”
Section: Structural Maintenance Of Chromosomes Flexible Hinge Domain Containing 1 (Smchd1)mentioning
confidence: 48%
“…It acts via distinct receptors, G-protein coupled receptor (GnRH) found in gonadotropes to induce production of the gonadotropin hormones, follicle and luteinizing -stimulating hormones (FSH), (LH) (85). a study found that congenital anosmia (loss of smell) is frequently linked with GnRH deficiency in human patients, leading to the widely held belief that GnRH neurons rely on olfactory structures to reach the brain, but this suggestion has yet to be proven (86).…”
Section: Retinoic Acids Covid-19 Nervous and Ocular Systemmentioning
confidence: 99%
“…The role of alterations of olfactory/vomeronasal patterning on defective GnRH neuron migration and olfactory dysfunction is still not well clarified 17 19 . However, relatively normal reproductive functions, or a late-onset hypogonadism, have been described in sporadic patients with congenital olfactory agenesis with anosmia 20 , 21 ; moreover, data from eugonadal patients with arrhinia show that human GnRH neurons may not entirely depend upon olfactory structures for their normal migration and function 22 . Studies on animal models unravelling the common origin of olfactory cells and a subpopulation of GnRH neurons from the neural crest 23 , an embryonic region that gives rise to the peripheral nervous system, bone, and melanocytes, may provide an additional interpretation of the syndromic association of hypogonadism and anosmia.…”
Section: The Extraordinary Journey Of Gnrh Neuronsmentioning
confidence: 99%